Ανθρωποκεντρικός Σχεδιασμός Γέφυρας Πλοίου - Φουσιάνης, Αθανάσιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2014)
Human Centred Design in naval architecture. Explanation of the importance of this new designing method that looks up to make ships safer, more ergonomic and more friendly to the user. Also detailed analysis of all methods' phases and guidelines for human centred design of the ship bridge.